Gliricidia (Gliricidia sepium) as an aid for enhancing soil health and crop productivity - Meena, B P; C, Shinogi K; Gurav, Pirya; Meena, V D; Lakaria, B L; Biswas, A K; Patra, A K (Indian Farming, 2021)
Gliricidia (Gliricidia sepium) can be raised in all type of soils and environment for cultivation and suitable for sole crop, intercrop, alley cropping or any other cropping system particularly in rainfed ecosystem. Hence, farmers should be encouraged to raise the Gliricidia on boarder of farm ponds, farm bunds, and borders of agricultural fields. Addition of Gliricidia as green leaf manure or mulch in crop production systems along with chemical fertilizers enhanced the crop yield along and soil health through improving soil physical, chemical and biological properties of soil.